Tuning Omniphobicity via Morphological Control of Metal–Organic Framework Functionalized Surfaces. - Tan, Tristan T. Y.; Reithofer, Michael R.; Chen, Eric Y.; Menon, Ajay G.; Andy Hor, T. S.; Jianwei Xu; Jia Min Chin (Journal of the American Chemical Society, 2013)
Fabrication of microstructures for imparting omniphobicity to a surface generally requires the use of lithographic techniques and specialized equipment. We report instead a simple strategy for the synthesis of microstructured surfaces via metal–organic framework (MOF) self-assembly. Our method allows us to localize epitaxial growth of MOF at the tips of needle crystals to create mushroom-shaped structures, thus conferring re-entrant textures to the MOF-functionalized surfaces. These structures synthesized via wet chemistry were found to have omniphobic properties due to the resulting re-entrant texture.